0=x^2-2xy+y^2-x^2y+xy^2-y0=x2−2xy+y2−x2y+xy2−y
0=x^2+y^2-2xy-x^2y+xy^2-y0=x2+y2−2xy−x2y+xy2−y
use formulas:
x^2+y^2=r^2,x=rcostheta,y=rsinthetax2+y2=r2,x=rcosθ,y=rsinθ
0=r^2-2rcosthetaxxrsintheta-r^2cos^2thetaxxrsintheta+rcos thetaxxr^2sin^2theta-rsintheta0=r2−2rcosθ×rsinθ−r2cos2θ×rsinθ+rcosθ×r2sin2θ−rsinθ
0=r^2-2r^2sinthetacostheta-r^3sinthetacos^2theta+r^3sin^2thetacostheta-rsintheta0=r2−2r2sinθcosθ−r3sinθcos2θ+r3sin2θcosθ−rsinθ
0=r^2-r^2(2sinthetacostheta)-1/2 r^3costheta(2sinthetacostheta)+1/2r^3 sintheta(2sinthetacostheta)-rsintheta0=r2−r2(2sinθcosθ)−12r3cosθ(2sinθcosθ)+12r3sinθ(2sinθcosθ)−rsinθ
0=r^2-r^2sin(2theta)-1/2 r^3costhetasin(2theta)+1/2r^3sinthetasin(2theta)-rsintheta0=r2−r2sin(2θ)−12r3cosθsin(2θ)+12r3sinθsin(2θ)−rsinθ